Semi-batch operation and countercurrent extraction by supercritical CO2 for the fractionation of lemon oil - Kondo, M; Akgun, N; Goto, M; Kodama, A; Hirose, T (ELSEVIER SCIENCE BV, 2002)
The supercritical fluid extraction of cold-pressed lemon oil was carried out in semi-batch and continuous countercurrent. modes. In order to observe the extraction behavior of lemon oil, semi-batch extraction was performed using a rectification column, and the distribution curve for the main constituents of lemon oil was obtained. Separation was improved by applying an internal reflux induced by a temperature gradient along the column. The effects of the reflux. on the extraction ratio, the separation selectivity, the concentration factor of each component and the recovery of oxygenated compounds were investigated for continuous operation at pressures of 8.8 and 9.8 MPa. Extraction combined with side-stream withdrawal was useful for lemon oil processing. The continuous operation with a linear temperature gradient from 313 to 333 K at 8.8 MPa showed the highest selectivity. Selectivity increased with the increase in solvent-to-feed (S/F) ratio. (C) 2002 Published by Elsevier Science B.V.
Keywords: lemon oil; deterpenation; countercurrent extractor; limonene; citral; linalool; VAPOR-LIQUID-EQUILIBRIA; DIOXIDE PLUS LIMONENE; CARBON-DIOXIDE; CITRUS OIL; REMOVAL; Chemistry; Engineering